Pola Akronim pada Istilah Bahasa Politik dalam Kampanye Anies Baswedan dan Muhaimin Iskandar (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Language is an arbitrary system of sound symbols used by humans to interact. One of its variations is political language, employed by political elites and bureaucracies to convey their power interests. Political language often utilizes euphemisms and propaganda to influence public opinion. In Indonesia's general election campaigns, political terms become integral to communication strategies. This study aims to analyze the use of political language in the campaigns of Anies Baswedan and Muhaimin Iskandar, focusing on the types of political terms and acronyms employed. Abdul Chaer's theory of language variation serves as the theoretical framework to understand how language reflects social identity and power relations within society. The research adopts a qualitative descriptive approach, analyzing sentences containing political terms from statements made by Anies Baswedan and Muhaimin Iskandar, sourced from YouTube videos on MetroTV and KompasTV channels. Identified terms include "identity politics," "black campaign," "electability," "coalition," "opposition," "regime," and "buzzer." Additionally, the study uncovers 11 acronyms effectively used in campaign communications. The findings provide insights into the strategic use of political language and its impact on public perception during electoral campaigns.